2020
DOI: 10.1097/mao.0000000000003031
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome of the Healthy External Auditory Canal

Abstract: Objective: To investigate the microbiota of the healthy external auditory canal (EAC) culture-independently and to evaluate the usefulness of the swabbing method in collecting EAC microbiota samples. Study Design: Cohort study. Patients: Fifty healthy asymptomatic working-age volunteers. Intervention: Samples were harvested with DNA-free swabs from the volunteers' EACs. Main Outcome Measures: Amplicon sequencing of the 16S rRNA gene was used to characterize the microbial communities in the samples. Results: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
1
18
1
Order By: Relevance
“…Our microbiome results have several differences from previous reports [ 19 , 31 ]. Microbiome composition is affected by many factors, such as the host genome, age, sex, family history, nutrition, and hormones.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our microbiome results have several differences from previous reports [ 19 , 31 ]. Microbiome composition is affected by many factors, such as the host genome, age, sex, family history, nutrition, and hormones.…”
Section: Discussioncontrasting
confidence: 99%
“…Sebaceous skin sites are dominated by Propionibacterium and Staphylococcus , whereas Corynebacterium prefers moist sites [ 16 ]. Ear canal skin apocrine (ceruminous) and sebaceous glands have been analyzed [ 18 ], but there are few studies on the microbiome of the human ear canal [ 19 ]. In a culture study, Staphylococcus was the most abundant taxon, followed by Corynebacterium and Streptococcus [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since its discovery, it has been highly controversial as to whether A. otitidis is truly a pathogen or merely a commensal of the external auditory canal [6]. This is mainly because the organism could be found in the external auditory canal (EAC) of apparently healthy individuals [14]. In a recent study, Sjovall et al, reported that EAC samples with a high relative abundance of Staphylococcus typically had a low abundance of Alloiococcus and vice versa.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…COM, chronic suppurative otitis media (0.05% and 0.04%, respectively). 6 In contrast, common bacteria in acute otitis media, such as Haemophilus influenzae, Moraxella catarrhalis, Streptococcus pneumoniae, A. otitidis, and T. otitidis, 28,39 were extremely rare (<0.05%) in samples from both diseases.…”
Section: Microbiota Characteristicsmentioning
confidence: 97%
“…The bacterial cells that colonize the skin and mucosa outnumber human cells, and these complex microbial communities have a large impact on human health and disease 1 . The microbiota of the healthy external auditory canal (EAC) is longitudinally stable 2 and well characterized; the dominant commensals are Staphylococcus auricularis (abundance:28.7%), Alloiococcus otitidis (19.5%), Turicella otitidis (18.3%), and Cutibacterium acnes (15.4%), while pathogenic bacteria, such as Pseudomonas aeruginosa , and Staphylococcus aureus , are extremely rare 3–6 . However, when colonizing bacteria migrate through the retraction pocket or a tympanic perforation, they may form biofilms to survive in this abnormal environment, and alter the microbiota 7,8 .…”
Section: Introductionmentioning
confidence: 99%